ANALYSIS OF SERVICE QUALITY AND SATISFACTION LEVEL OF CUSTOMERS IN BANKING SECTOR OF BANGLADESH - Shahidul Islam, Md.; Niaz, A.Z.M (British Journal of Marketing Studies, 2014)
The major aim of the study are to evaluate the customer satisfaction of the service quality and to assess whether bank services provided by the institutions are satisfactory to Bangladeshi customers especially in term of service categories. This study endeavors to discover the impact of service quality on customer satisfaction in banking sectors. The study also examines empirically the determinants of service quality in Bangladesh. Five dimensions in service quality such as Initial Experience, Delivery Service Condition, Service Experience, Relationship & Environment and Grievance Handling are considered as the base for this study. A questionnaire for such purpose was designed and different statistical methods were applied to analyse the collected data. Here 300 customers who conduct consumer banking were interviewed with a structured questionnaire. Cross tabulation, a technique of descriptive statistics, used to determine the variability of five dimensions. The correlation results indicate that there is a positive correlation between the dimensions of service quality and customer satisfaction. Furthermore, the multiple regression analysis, a technique of multivariate analysis, adopted to determine the importance of the perceived service quality factors. The results of the regression test showed that offering quality service have positive impact on overall customer satisfaction. That is, service quality dimensions are crucial for customer satisfaction in banking sector in Bangladesh.